2009
DOI: 10.1159/000258135
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Multiple Forms of proGRP in Serum from Small Cell Lung Cancer Patients

Abstract: To determine whether various forms of progastrin-releasing peptide (proGRP) exist in the human circulation, a panel of monoclonal antibodies was produced to construct immunometric assays for various proGRP fragments. In combination with liquid chromatography, this facilitated the determination of fragment size distribution in the sera of patients with small cell lung cancer (SCLC). Separation of proGRP peptides from SCLC cell lines and patient samples by ion exchange and gel filtration resulted in the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Although these studies had shown decreased neutrophil infiltration within inflamed foci, a possible direct effect of this molecule on neutrophils was not considered until we showed that RC can prevent neutrophil migration in GRP‐induced peritonitis . GRP release in the serum correlates with rheumatoid arthritis , asthma , atopic dermatitis , and cancer . Here, however, although no GRP was found in serum of mice with DILI, treatment with RC impaired neutrophil migration in vivo and in situ.…”
Section: Discussionmentioning
confidence: 76%
“…Although these studies had shown decreased neutrophil infiltration within inflamed foci, a possible direct effect of this molecule on neutrophils was not considered until we showed that RC can prevent neutrophil migration in GRP‐induced peritonitis . GRP release in the serum correlates with rheumatoid arthritis , asthma , atopic dermatitis , and cancer . Here, however, although no GRP was found in serum of mice with DILI, treatment with RC impaired neutrophil migration in vivo and in situ.…”
Section: Discussionmentioning
confidence: 76%
“…The greater stability of the Elecsys® ProGRP assay in serum, relative to the ARCHITECT assay, most likely relates to the antibody-binding sites on the ProGRP peptide. The two monoclonal antibodies in the Elecsys® ProGRP assay bind to epitopes that are relatively resistant to endoproteolytic cleavage [16,17,26], whereas the two monoclonal capture antibodies in the ARCHITECT assay bind directly next to the thrombin-cleavage site (Supplementary Fig. S1).…”
Section: Discussionmentioning
confidence: 99%
“…The Elecsys® ProGRP assay (Roche Diagnostics GmbH, Penzberg, Germany) is a new immunoassay designed to quantitatively determine levels of ProGRP in both human serum and plasma. As the two monoclonal antibodies in the Elecsys® ProGRP assay bind to epitopes in the ProGRP peptide that are relatively resistant to endoproteolytic cleavage [16,17,26] (Supplementary Fig. S1), serum samples as well as plasma samples can be used.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of investigating expression of the ProGRP isoform in relation to diagnosis and disease was presented earlier. 19 However, to our knowledge, this will be the first report proving the existence of ProGRP isoforms on a protein level. Differentiation between these isoforms could be of clinical value, as well as offering insight into SCLC biology.…”
Section: Introductionmentioning
confidence: 74%